Impact of Biofertilizer and Inorganic Fertilizers on Soil Available Phosphorus, Productive Tillers, and Rice (Oryza sativa L.) Yield - Ngui, Marianus; Melati, Maya; Muhimmatul, Husna (UNIVERSITY OF LAMPUNG, 2024)
The use of Bacillus bacteria as biofertilizers (BF) increases since the detrimental effects of inorganic fertilizers on the agricultural environment spread out. The objective of this research was to study the influence of bio fertilizer and in combination with inorganic fertilizer on the productivity of rice fields. The experiment was a two-factor treatment arranged in a split-plot design with three replications using a randomized complete block design (RCBD). The first factor was fertilizers, which were used as the main plot. The second factor was paddy varieties as a subplot. The results showed that the combination of inorganic and bio fertilizer application of (150 kg NPK ha-1 + 75 kg Urea ha-1 + 4 L BF ha-1) and (300 kg NPK ha-1 + 150 kg Urea ha-1 + 4 L BF ha-1), improved soil available phosphorous (P) of 12.04%, 40.69%, and 44.05%, respectively compared to control treatment, the inorganic fertilizer application (300 kg NPK ha-1 + 150 kg Urea ha-1), and the bio fertilizer application (4 L BF ha-1). In addition, the application of (300 kg NPK ha-1 + 150 kg Urea ha-1 + 4 L BF ha-1) increased productive tillers per plant as 28.13% and 16.48% compared to the control and the inorganic application, respectively. Moreover, by using Mekongga variety, applying the inorganic and bio fertilizer at rates of (300 kg NPK ha-1 + 150 kg Urea ha-1 + 4 L BF ha-1) increased rice yield of 64.08% and 30.33% compared to the control and the inorganic fertilizer application; while, by using IPB 3S variety, the rice yield increased by 85.80% and 10.34%, respectively. These findings are significant as they demonstrate the potential of biofertilizers to enhance soil fertility and rice productivity, thereby advancing sustainable farming practices.